Relevansi Pemikiran Ibn Khaldun Terhadap Sistem Presidential Threshold Di Indonesia - Khusnul Khotimah, Nur (El-Dusturie, 2024)
The aim of writing this scientific article is to find out about Ibn Khaldun's thoughts on the conditions for limiting the requirements for candidates for head of state and their relationship to the Presidential Threshold system in Indonesia. The presidential threshold is a rule established by an authorized institution which becomes a reference in presidential candidacy, this reference is in the form of a limit obtained from support from the DPR, support obtained in the form of votes (ballot) or results of obtaining seats (seat). These limits must be obtained by political parties or combinations of political parties in order to be able to nominate President in the General Election. The implementation of the presidential threshold is a policy that aims to create stability between the government and the legislative body so that the government does not encounter difficulties in taking policy direction. In Islamic teachings, majority power can be limited, so that popular sovereignty means the people's right to supervise the government to always remain within the limits outlined by the Shari'a. The people of Medina, who are the reference for the concept of an Islamic state, have a political idea called shura' (deliberation), namely an open space where anyone has the right to express their opinion in an area where the Shari'ah does not strictly limit it. Shura' exceeds democracy in terms of the availability of sharia which limits majority rule which allows the growth of authoritarianism under the guise of democracy. The concept of shura' is very relevant to democracy, especially in the aspects of substance, spirit of opposition to tyranny, and the principle of the majority. Through the concept of shura', the state in Islam must open up space for interaction for society as part of a mechanism for political control and participation as part of worship and amar ma'ruf nahi munkar. From the results of this research, it can be concluded that there is relevance between the Presidential Threshold and Ibn Khaldun's thoughts regarding one of the requirements for a person to be nominated as head of state.